Non-traditional data to inform modern climate science - Miner, Kimberley R.; Wong, Ethan; Gay, Bradley A.; Miller, Charles E. (Frontiers in Communication, 2025)
The global climate is changing rapidly, with cascading impacts across the world. Even though the modern instrument-based record of Earth observations reflects decades of critical work, multi-century time series may be required to understand and forecast key elements of Earth system dynamics. Here, we review the potential uses of non-traditional climate data records—observations reported without using modern instruments or standardized measurement protocols—to identify climate and ecosystem dynamics that predate modern methodologies and tools. We compile a list of diverse datasets collected over more than 500 years, including landscape paintings, sea lore, and animal migration data. This initial review presents opportunities for further investigation to reconstruct past climate or to use non-traditional records to complement modern instrument methods.